Prevalence of Infertility by Clinical, Epidemiological, Demographic Definitions and its Determinants in Tehran, Iran - Hajiieh Bibi Razeghi-Nasrabad; Meimanat Hosseini-Chavoshi; Mohammad Jalal Abbasi-Shavazi (مجله دانشگاه علوم پزشکی گرگان, 2022)
Background and Objective: Infertility is one of the issues that affect many aspects of infertile couples. In this study current infertility in Tehran province is estimated based on clinical, epidemiological and demographic definitions. Methods: This descriptive-analytical study was performed on 669 women with a spouse aged 15-49 in Tehran, Iran during 2020. Data were collected by using a valid researcher-made questionnaire. Results: Prevalence of current infertility by clinical, epidemiological and demographic definitions was 9.6%, 8.1% and 5.8%, respectively. As expected, primary infertility is lower (2%-4%) than secondary infertility (1.8%-6.4%). Some couples become infertile after their first pregnancy and the birth of their first child. Infertility has a significant relationship with age (P<0.05), age in the first marriage (P<0.05) and socio-economic statuse (P<0.05). Conclusion: Current primary infertility is relatively low and normal, but secondary infertility is high. Focus on lifetime infertility shows higher rates of infertility than current infertility in Tehran, Iran.